Reality of the dispute settlement of construction contracts by the judiciary in Iraq - Raid Saleem Abd Ali; Nooran Kanaan Yassin (Wasit Journal of Engineering Sciences)
This study deals with the dispute settlement of construction contracts by the judiciary in Iraq, as well as identifying the reasons that contribute to these conflicts occur. Scientific methodology was followed by the collection data about contracting construction (51) contracts, where conflicts have occurred between the contractor and the employer and that the impact has been to resort to the judiciary to resolve them, As well as data collection for the (83) case of ʺpenalty taking work from contractorsʺ. The research is found that there are seventeen reasons for the occurrence of disputes between the contractor and the employer, the (employer's delay in the disbursement of the financial duties of the contractor) occupy first rank and a percentage of (22.73%), follow in the second rank (default by the employer in the removal of the obstacles that objects the contractors works) and by (10.6%), but (delete, add, or the introduction of new clauses on quantities) and (delay of the employer to receive the carried work preliminary or final) occupy third rank with (9.09%). Litigation takes several years to resolve disputes in construction contracts.It is found that (95%) of the decisions (in the sample study cases) issued by the Court are based on the report of the experts engineers who are used to express their artistic opinion on a specific subject in the case.